2020
DOI: 10.3390/nu12061664
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Head Growth during Early to Mid-Gestation Associated with Weight Gain in Mothers with Hyperemesis Gravidarum: A Retrospective Cohort Study

Abstract: The epigenetic impact of malnutrition in mothers with hyperemesis gravidarum (HG) on their offspring has not been fully elucidated. Recently, several reports have demonstrated that children born to mothers with HG were small for gestational age and had low birth weight, reduced insulin sensitivity, and neurodevelopmental delays during childhood. Therefore, we examined the relationship between fetal growth and changes in the maternal body weight in HG cases. A total of 34 patients with HG were hospitalized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In contrast, Greater rate of gestational weight gain during the second and the third trimesters was associated with greater risk of large-for-gestational age neonates [2]. Our group has recently reported that in hyperemesis gravidarum, in which maternal undernutrition occurs in the first trimester of pregnancy, the pattern of foetal head growth differs from that of the normal pregnancy [3]. Moreover, the weight gain in slim and obese women should not be the same because of the differences in their nutritional demands during pregnancy.…”
Section: Maternal Weight Gain During Pregnancymentioning
confidence: 85%
“…In contrast, Greater rate of gestational weight gain during the second and the third trimesters was associated with greater risk of large-for-gestational age neonates [2]. Our group has recently reported that in hyperemesis gravidarum, in which maternal undernutrition occurs in the first trimester of pregnancy, the pattern of foetal head growth differs from that of the normal pregnancy [3]. Moreover, the weight gain in slim and obese women should not be the same because of the differences in their nutritional demands during pregnancy.…”
Section: Maternal Weight Gain During Pregnancymentioning
confidence: 85%
“…Maternal malnutrition in the first trimester of pregnancy can be caused by hyperemesis gravidarum because it results in malnutrition, electrolyte imbalance, and poor fetal development, such as prematurity and low birth weight (Santosa, Arif, & Ghoni, 2022). This condition is closely related to stunting because it can affect the growth and development of the fetal brain, which results in an increased risk of neurodevelopmental delays in the future (Buyukkayaci Duman et al, 2015;Muraoka et al, 2020). A research result revealed that children with hyperemesis gravidarum mothers have behavioral disorders (Fejzo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The next step is to create an item pool based on a literature review into 10 items, namely mid upper arm circumference (MUAC) (Agustina & Fathurrahman, 2022;Alfarisi, Nurmalasari, & Nabilla, 2019;Sukmawati, Hendrayati, Chaerunimah, & Nurhumairah, 2018); height (Khatun, Rasheed, Alam, Huda, & Dibley, 2019;Nadiyah, Briawan, & Martianto, 2014;Özaltin, Hill, & Subramanian, 2010); weight gain during pregnancy (Apriningtyas & Kristini, 2019;Dewi, Evrianasari, & Yuviska, 2020); consumption of Fe tablets (Ashorn et al, 2015;Dewey, 2016;Georgieff, 2020); excessive nausea and vomiting during pregnancy (Buyukkayaci Duman, Ozcan, & Bostanci, 2015;Muraoka, Takagi, Ueno, Morita, & Nagano, 2020); maternal age (Wanimbo & Wartiningsih, 2020;Wemakor, Garti, Azongo, Garti, & Atosona, 2018); mother's smoking habits and history of exposure to cigarette smoke (Ashford et al, 2010;Nadiyah et al, 2014;Stock & Bauld, 2020); birth spacing (Anasari & Suryandari, 2022;Karundeng, Ismanto, & Kundre, 2015;Pongrekun, Sunarsih, & Fatmawati, 2020); mother's education (Komalasari, Supriati, Sanjaya, & Ifayanti, 2020;Scheffler et al, 2021).…”
Section: Measures and Covariatesmentioning
confidence: 99%